The Celestine Prophecy : An Adventure - Redfield, James (London Bantam Books, 1997)
Drawing on the ancient wisdom found in a Peruvian manuscript, this book tells you how to make connections between the events happening in your own life right now, and lets you see what is going to happen to you in the years to come.
Keywords: Peru -- Spiritual life -- Manuscripts--Collectors and collecting -- Celestine prophecy (Redfield, James)